Enhanced degradation of perfluorooctanoic acid by a genome shuffling-modified Pseudomonas parafulva YAB-1. Issue 24 (28th October 2019) - Yi, Langbo; Peng, Qingzhong; Liu, Deming; Zhou, Lulu; Tang, Chongjian; Zhou, Yaoyu; Chai, Liyuan
ABSTRACT: Perfluorooctanoic acid (PFOA) as an emerging persistent organic pollutant is hard to be degraded by conventional methods because of its stable physical and chemical properties. Microbial transformation is an attractive remediation approach to prevent and clean up PFOA contamination. To date, several strains of wild microbes have been reported to have limited capacity to degrade PFOA, selection of superior strains degrading PFOA become urgently necessary. Here, we report the application of genome shuffling to improve the PFOA-degrading bacterium Pseudomonas Parafulva YAB-1. The initial mutant populations of strain YAB1 were generated by nitrosoguanidine and ultraviolet irradiation mutagenesis respectively, resulting in mutants YM-9 and YM-19 with slightly improved PFOA-degrading ability. YM-9 and YM-19 were used as the starting strains for three rounds of recursive protoplast fusion. The positive mutants were screened on inorganic salt medium plates containing different concentrations of PFOA and selected based on their PFOA degradability in shake-flask fermentation test. The best performing recombinant F3-52 was isolated after three rounds of genome shuffling. In batch fermentation, the PFOA degradation rate of mutant F3-52 was up to 58.6%, which was 1.8-fold higher than that of the parent strain YAB1, and 1.6-fold higher than the initial mutants YM-9 and YM-19. Pass-generation test indicated that the heredity character of F3-52 was stable. The results demonstrated that genome shuffling was an efficient method for improving PFOA degradation of Pseudomonas Parafulva YAB1. The bred mutant F3-52 with 58.6% PFOA-degrading rate could be used for the environmental control of PFOA pollutant. GRAPHICAL ABSTRACT: